Beyond genes: A systematic review of environmental risk factors in specific reading disorder. (November 2018) - Mascheretti, Sara; Andreola, Chiara; Scaini, Simona; Sulpizio, Simone
Highlights: We reviewed the literature on environmental risk variables implicated in reading disorder. We did a systematic review in PubMed, Scopus, PsycINFO with no time restriction. Gestational weeks and birth weight reliably predicted reading readiness and reading disorder. SES and home literacy environment are good life-long risk predictors of reading skill. Environmental risk factors are also reviewed in their interaction with genetic signal. Abstract: Background: While an understanding of the genetic contributions to specific reading disorder (RD) is emerging, there is no agreement about which putative hazard factors are clearly involved in the aetiology of this disorder. Aims: A literature review looking at the impact of environmental risk variables implicated in RD either per se or when interacting with the genes. Methods and procedures: We performed a systematic literature review using the following keywords: dyslexia OR reading disability AND environmental risk factors OR environmental hazard factors, in the following electronic databases: PubMed, Scopus and PsycINFO, without any time restrictions. Outcomes and results: Gestational weeks and birth weight are among the pre- and peri-natal risk factors shown to reliably predict reading readiness and the odds of having RD. Inconclusive findings have been reported for maternal cigarette smoking, family history of psychiatric and medical diseases, and risk of miscarriage. A broad definition of familial socio-economic status and home literacy environment have been identified as good life-long risk predictors of reading skills. Conclusions and implications: We highlighted the need to consider environmental hazards, their interactions and interactions with RD-candidate genes in the study of the aetiology of RD in order to provide much-needed insight into how these variables influence reading skills.